A systematic review of the management of synthetic mesh erosion of the rectum following urogynaecological surgery. (23rd July 2019) - Younan, H‐C.; Machin, M.; Myers, A. F.; Slesser, A. A. P.; Mohsen, Y.
Abstract: Aim: Synthetic rectal mesh erosion is a challenging complication following urogynaecological surgery. The aim of this study was to determine the optimal management of rectal mesh erosion following urogynaecological surgery. Method: A systematic review was undertaken following a pre‐defined protocol registered with PROSPERO (CRD42018112425) in accordance with PRISMA guidelines. Searches of MEDLINE online database, Cochrane Library and clinical trial registries (ClinicalTrials.gov, EU Clinical Trials, ISRCTN registry) were performed. The included articles were heterogeneous – therefore a narrative synthesis was performed. Results: Fourteen studies were included in the review: 11 case reports, one case series, one retrospective cohort and one prospective multicentre trial. Fourteen rectal mesh erosions were identified. Eight (57%) of the rectal erosions underwent major abdominal surgery. In two of these cases, the abdominal approach was used only after failure of the transanal route. Five (36%) of the mesh erosions were managed using a transanal approach. In one case, the mesh passed without intervention. Conclusion: Synthetic rectal mesh erosion can be managed successfully via either a transanal or a transabdominal approach with a partial or complete excision of the mesh. An examination under anaesthetic with an attempted transanal removal of mesh should be considered the first step in the management of this condition before consideration of more invasive surgery.